2020
DOI: 10.1007/s00391-020-01734-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurogeriatrics—a vision for improved care and research for geriatric patients with predominating neurological disabilities

Abstract: Geriatric medicine is a rapidly evolving field that addresses diagnostic, therapeutic and care aspects of older adults. Some disabilities and disorders affecting cognition (e.g. dementia), motor function (e.g. stroke, Parkinson’s disease, neuropathies), mood (e.g. depression), behavior (e.g. delirium) and chronic pain disorders are particularly frequent in old subjects. As knowledge about these age-associated conditions and disabilities is steadily increasing, the integral implementation of neurogeriatric know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…First, due to the cross-sectional study design, we cannot draw conclusions regarding the causality of relationships. Second, this is a heterogeneous study cohort representing geriatric patients with predominating neurological disabilities with acute onsets and chronic disease courses ( 13 ), thus we cannot draw definite conclusions for patients with specific diseases and also cannot adjust the analyses for disease-related confounders (e.g., freezing in patients with PD). Third, we did not include measures of physical activity and anxiety, and we had to rely on self-reported retrospective falls assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, due to the cross-sectional study design, we cannot draw conclusions regarding the causality of relationships. Second, this is a heterogeneous study cohort representing geriatric patients with predominating neurological disabilities with acute onsets and chronic disease courses ( 13 ), thus we cannot draw definite conclusions for patients with specific diseases and also cannot adjust the analyses for disease-related confounders (e.g., freezing in patients with PD). Third, we did not include measures of physical activity and anxiety, and we had to rely on self-reported retrospective falls assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to a deconditioning effect on muscle strength and balance, aggravating a downward spiral towards functional decline (2,5,9,10). Neurological diseases such as stroke/small vessel disease, vertigo, Parkinson's disease (PD) and polyneuropathy (PNP) have been identified as risk factors for falls (2,(11)(12)(13) with the prevalence of falls among neurological in-patients being almost twice as high as in an age-matched population (14). FOF was identified as a risk factor for future falls in neurological patients (14,15) and is negatively correlated with health-related quality of life in patients with PD (16,17) and stroke (18).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have indicated that patients might benefit from this approach [ 4 , 5 ]. However, there are a number of factors that may influence a patient’s functional abilities as well as their ability to recover [ 6 , 7 ]. In particular, disorders of the central nervous system such as ischemic or hemorrhagic stroke, tumors, epilepsy, encephalopathy, delirium, or dementia may cause deficits and affect rehabilitation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a number of factors that may influence a patient’s functional abilities as well as their ability to recover [ 6 , 7 ]. In particular, disorders of the central nervous system such as ischemic or hemorrhagic stroke, tumors, epilepsy, encephalopathy, delirium, or dementia may cause deficits and affect rehabilitation [ 6 , 7 ]. Electroencephalography (EEG) is an established neurological procedure that provides valuable information for estimating and monitoring cerebral function and determines cognitive performances [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…B. [5,8]). Ebenso ist psychiatrische Versorgung im Allgemeinen und gerontopsychiatrische Tätigkeit im Speziellen ohne eine solche Perspektive nicht denkbar.…”
unclassified